KRI DESIGN AND MITIGATION STRATEGY ON WATER DISTRIBUTION OF PERUMDA AIR MINUM MAKASSAR REGIONAL IV: A Case Study - Yan Herdianzah (Center for Study and Journal Management FTI UMI, 2020)
Municipal Waterworks Corporation (PERUMDA AIR MINUM) of Makassar city currently finds many common risks in water distribution process. The risks cause a lot of damage to the piping network system, so that the quantity of distributed water to customers is not optimal. Consequently, it is necessary to handle the risks. This study aims to determine the risks that occur in water distribution process by using Delphi method to identify potential risks. Then, House of Risk (HOR) is used at the risk analysis and evaluation stage to determine mitigation strategies and Key Risk Indicators (KRI) is designed to determine the Early Warning System (EWS). Based on the results known that there are 16 identified risk events and 24 risk agents. Furthermore, a mitigation strategy is carried out on the risk agent by using 18 preventive actions. Based on the selected risk, coded as A24 with the indicator value is Information (Field Team) has lower threshold of 5 hours and upper threshold of 8.19 hours. Water loss has lower threshold of 3,118,047 m3 and upper threshold of 3,283,688 m3. A1 as Expired indicator value has lower threshold of 20 years and upper threshold of 26 years and leaking pipes replacement has lower threshold of 15 years and upper threshold of 16 years 3 months 2 weeks. Further research is expected to be able to design KRI for the risks that do not have EWS yet.